Multidimensional index of academic risk in FIEECS-UNI undergraduate students - Ordoñez Mercado, Alipio Francisco (2018)
In this work, the impact of academic risk on academic performance is determined by constructing a scale to calculate the multidimensional index of academic risk, using the statistical technique of factor analysis, which explains 83.274% of the total variation and is made up of six dimensions and 42 items. The most important dimension is the student's personal attitudes (X1), followed by family support (X2) and the teaching domain (X3). The impact of academic risk on performance is inverse and significant, reaching a linear correlation of r = - 0.214, which translates into a decrease of 0.191 points in academic performance for each point in academic risk. It was also determined that the dimension of the teaching domain (X3) has a highly significant and inverse impact on the student's academic performance, quantified as a decrease of 0.255 for each point in the teaching domain.